Pengaruh Intellectual Capital dan Good Corporate Governance terhadap Financial Performance - Alma, Maf'ula Asfida; Listyani, Indah; Murdiyanto, Edi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The shift from labor-based companies to knowledge-based businesses, including in the banking industry, encourages the role of intellectual capital dan corporate governance in determining financial performance. The object of this research is banking companies listed on the IDX in 2017 - 2021. The sample size was determined using a purposive sampling approach which produced 50 data. Regression on panel data is used to test the hypothesis. The research results show that the number of board of commissioners dan the frequency of board of commissioners meetings do not have a major impact on financial performance. However, intellectual capital, independent commissioners dan managerial ownership have a big influence on financial performance. This study shows that the responsibility of the board of commissioners is only to comply with the regulations. On the other hdan, the company's intellectual capital has been managed well dan is able to generate long-term profitability. Therefore, the business world must manage its intellectual capital dan corporate governance effectively dan efficiently in order to continue to exist dan maintain the trust of its stakeholders.